Single-Lung Transplantation in the Setting of Aborted Bilateral Lung Transplantation - Varun Puri; Tracey Guthrie; Masina Scavuzzo; Daniel Kreisel; Alexander S. Krupnick; G. Alexander Patterson; Bryan F. Meyers (Journal of Transplantation)
Background. The outcome of patients undergoing a single-lung transplant in the setting of an aborted bilateral lung transplant is unclear. Methods. A retrospective review of single lung transplants at an institutional program. Results. Of the 543 lung transplants performed over the last 10 years, 31 (5.7%) were single-lung transplants. Nineteen of 31 (61%) were planned single-lung transplants, while 12/31 (39%) were intraoperatively aborted, double lung transplants converted to single-lung transplants. The aborted and planned groups were similar in age, lung allocation score and NYHA status. The reasons for aborted double lung transplantation were cardiac/hemodynamic instability 4/12 (33%), difficult pneumonectomy 3/12 (25%), size mismatch 4/12(33%), and technical issues 1/12 (8%). The aborted group had higher CPB utilization (5/12 versus 1/19, 𝑃=.02), similar ischemic times (260 versus 234 min) and similar incidence of grade 3 primary graft dysfunction (6/12 versus 3/19, 𝑃=.13). ECMO was required for graft dysfunction in 2 patients in the aborted group. The one and two-year survival was 84% and 79% in the planned group and 62% and 52% in the aborted group, respectively. Conclusions. Patients undergoing single-lung transplantation in the setting of an aborted bilateral lung transplant may be at a higher risk of worse outcomes.